PENGELOLAHAN JAGUNG SECARA OTOMATIS SEBAGAI PAKAN UNGGAS - Paramytha, Nina; Hidayat Oktapianus, Hengki (Ensiklopedia of Journal, 2024)
Corn drying and shelling devices are essential equipment in the poultry feed industry. This research aims to develop an efficient and automated device for drying and shelling corn as poultry feed. This device utilizes a modified corn sheller machine equipped with a DHT22 sensor to monitor the temperature and humidity of the air surrounding the device, as well as a soil moisture sensor to monitor the moisture content of the processed corn. Additionally, a heater is integrated to aid in the corn drying process. The research method employed includes the stages of design, development, and testing of the device. The design stage involves conceptual design based on technical and functional requirements. Development is carried out by modifying the corn sheller machine, installing sensors, and integrating the heater. Testing is conducted to ensure the performance of the device in drying and shelling corn efficiently and accurately. The results show that the developed device is capable of drying and shelling corn effectively. The DHT22 sensor and soil moisture sensor successfully monitor environmental conditions and corn moisture in real-time, allowing for optimal drying process control. The integrated heater helps improve the efficiency of corn drying, thereby reducing the time required for the process. In conclusion, the developed corn drying and shelling device can serve as an effective and efficient solution for producing poultry feed automatically. The integration of sensors and heater provides better control over the drying process, resulting in high-quality products with more efficient time and energy utilization. This research contributes to the development of environmentally friendly and sustainable agricultural technology. Key Words: Corn Dryer and Sheller, automatic, DHT22, Heater, Soil Moisture